Improved characterization of thin bed and low-resistivity/low-contrast hydrocarbon reservoirs / Hijaz Kamal Hasnan - Hijaz Kamal , Hasnan (2020)
Thin-bed and low-resistivity/low-contrast (LRLC) reservoirs such tidal heterolithic deposits contain a significant amount of the global hydrocarbon reserves. However, due to millimetre-to-centimetre thin sandstone, forecasting hydrocarbon reserves and production are challenging. Producing hydrocarbon economically from heterolithic deposits in thin-bed reservoirs requires the characterisation of flow properties in thin beds for improved hydrocarbon reserves and production estimates. Sedimentology interpretation of the study area and reservoir in Malaysia shows that heterolithic deposits are part of tidal bars in a shallow marine environment with a large areal extent that suggests the substantial volume of heterolithic deposits which represent potential hydrocarbon reserves. Conventional Well Logs and Experimental Core Analysis cannot resolve and represent the flow properties in millimetre-to-centimetre scale sandstone layers in heterolithic deposits, which resulted in underestimated hydrocarbon reserves estimates. Characterisation of flow properties in thin sandstone layers is the first step in a multiscale workflow in reservoir modelling that could improve hydrocarbon reserves estimates in heterolithic deposits. This thesis applied X-Ray Micro-CT Imaging and Analysis, Digital Core Analysis, gas permeability analysis and 3D Visualisation on five mini-plugs from the sand dominated regions of two muddy heterolithic core plugs, two laminated rock core plugs and one sandy heterolithic core plug that represent sandstone units in the reservoir. The main objectives are to characterise the porosity, permeability and connectivity of the thin sandstone layers in the heterolithic samples and investigate the multi-scale impact of small-scale heterogeneities such as average grain size and carbonate laminates on permeability. Computed porosities of the five mini-plugs are consistent with the experimental results that validated the computed porosity using digital core analysis. The computed permeability of a mini plug from one heterolithic core plug is similar to the results of the laminated sandstone mini-plugs which are benchmark reservoir sandstones. 3D visualisation of the heterolithic core plug reveals laterally continuous thin sandstone layers that are well connected and represent potential hidden sand pay and additional hydrocarbon reserves in heterolithic deposits. Permeability gas probe measurements of the surfaces of the core plugs validated the computed results of all samples. The results verified the presence of permeable thin sandstone layers in the heterolithic core plug. Also, 3D visualisation of the sandstone core plugs reveals carbonate minerals. The carbonate causes lower core plug permeability compared to their more homogeneous mini-plugs. This result highlights the multi-scale effects of small-scale heterogeneities on permeability at larger scales. Grain size analysis of all samples indicated that permeability increases with smaller average grain sizes and is the main factor in permeability difference between similar rock types. To sum up, the methodology used in this thesis characterised the permeability of wellconnected millimetre-to-centimetre scale reservoir sandstone layers in heterolithic deposits that represent additional net sand pay and potential hydrocarbon reserves in heterolithic deposits. Our methodology and results contribute to the first stages of a multiscale workflow for reservoir modelling of heterolithic deposits in thin-bed LRLC reservoirs. Our methods can incorporate the properties millimetre-to-centimetre scale sandstone layers and other small-scale heterogeneities into reservoir models for improved the hydrocarbon reserves and production forecasts.